2006
DOI: 10.1007/s10038-006-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the associations between the genes of 22q11 deletion syndrome and schizophrenia

Abstract: Schizophrenia is a severe, debilitating mental disorder characterized by profound disturbances of cognition, emotion and social functioning. The lifetime morbid risk is surprisingly uniform at slightly less than 1% across different populations and different cultures. The evidence of genetic risk factors is our strongest clue to the cause of schizophrenia. Linkage and association analyses have identified genes associated with the development of schizophrenia. However, most of the alleles or haplotypes identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 88 publications
(93 reference statements)
4
38
0
Order By: Relevance
“…For example, mental retardation associated with the 22q11 deletion syndrome is due to the combined effects of the haploinsufficient genes PRODH 23 and TBX1. 24 Our study has found that many haploinsufficient phenotypes describe developmental disorders and mental retardation, consistent with our finding that haploinsufficient genes are enriched in regulatory and developmental gene functions. SDs appear to be important in primate evolution and in shaping human genetic variation.…”
Section: Discussionsupporting
confidence: 92%
“…For example, mental retardation associated with the 22q11 deletion syndrome is due to the combined effects of the haploinsufficient genes PRODH 23 and TBX1. 24 Our study has found that many haploinsufficient phenotypes describe developmental disorders and mental retardation, consistent with our finding that haploinsufficient genes are enriched in regulatory and developmental gene functions. SDs appear to be important in primate evolution and in shaping human genetic variation.…”
Section: Discussionsupporting
confidence: 92%
“…Velopharyngeal dysfunction, palatal abnormalities, thymic hypoplasia, and hypoparathyroidism with resultant hypocalcemia occur commonly. There is a well-recognized increased incidence of schizophrenia (6%-30%) and behavioral disturbances [79]. Facial dysmorphism can be subtle, with hooded eyelids and a square shape of the nose being common features.…”
Section: Q112 Microdeletion Syndrome (Velo-cardiofacial Syndrome/dmentioning
confidence: 99%
“…43 Two relatively small studies indicate that the lifetime prevalence of schizophrenia is 25-30% for people with 22q11DS. [43][44][45][46] Compared with 22q11DS patients, only individuals who have a monozygotic co-twin with schizophrenia or two parents with schizophrenia have greater risk of developing schizophrenia. 43 Although schizophrenia is usually considered as an adultonset disorder, psychiatric disorders in childhood also occur in those with 22q11DS.…”
Section: Mental Illnessmentioning
confidence: 99%